A Proposed Framework for the Role of Inter-Cost Management Techniques in Reducing the Costs of Industrial Cluster Enterprises to Support their Business Environment Competitiveness: A Field Study in the Saudi Arabia - Aboelfadl, Abdelaal Mostafa; Ibrahim, Ayman Ahmed Youssef (Journal of Ecohumanism, 2024)
The research aims to demonstrate the role of intra-cost management in reducing the costs of industrial clusters in small and medium enterprises to support their competitiveness. In addition building a comprehensive proposal framework for inter-cost management tools that are compatible with the characteristics of industrial clusters in small and medium enterprises in the modern business environment. And the extent of the contribution of the dimensions of this proposed framework in reducing the costs of the industrial cluster in the Saudi industrial enterprises. The research reached the building of a comprehensive proposed framework for inter-cost management tools that are compatible with the characteristics of industrial clusters, and the development of the mechanism of action of this framework. In the field study, the contribution of the dimensions of the proposed framework was also reached in reducing the costs of industrial clusters to support their competitiveness in the Saudi business environment. This was done by achieving several advantages for the industrial cluster enterprises, including: Reducing the total costs along the supply chain to the lowest possible level. Improving the quality levels of products. Improving the indicators of profitability within all the industrial cluster parties. Generating innovative designs that meet the needs and desires of all customers. And the speed to the change in the tastes and requests of customers within the industrial cluster. And in terms of the relative importance of each of the dimensions of the proposed framework. In the first order, in terms of relative importance, came the contribution of inter-cost management tools associated with suppliers. In the second order, the contribution of inter-cost management tools in the pre-industrial .And in the third order, the contribution of inter-cost management methods in the manufacturing. Finally, the contribution of inter-cost management methods associated with customers t came in the fourth and final order in reducing costs and increasing the competitiveness of the industrial cluster facilities in the Saudi business environment.